2012
DOI: 10.1111/j.1399-3046.2012.01697.x
|View full text |Cite
|
Sign up to set email alerts
|

Conversion to sirolimus in pediatric renal transplant patients: A single‐center experience

Abstract: We studied efficacy and safety of conversion from CNI- to SRL-based immunosuppression in 92 kidney TX recipients, mainly due to CAN (69%). Median time of conversion was 31 months (r: 0.3-165); median time of follow-up: 36 months (r: 2-102). In the whole group mean eGFR increased from 53 ± 22 to 67 ± 26mL/min/1.73 m(2) at three months (p = 0.02) and did not change subsequently. Patients with grade I CAN had higher eGFR than those with grade II CAN. Patient and graft survival was 96% and 70% 10 yr after conversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Retrospective single‐center studies in which maintenance pediatric kidney transplant patients have been switched from a standard CNI regimen to an mTOR inhibitor with low‐dose CNI therapy or, more frequently, CNI‐free immunosuppression after introduction of everolimus or sirolimus have indicated that rejection is prevented effectively after conversion, but have generally included no more than 30 patients. Two prospective trials have evaluated conversion of patients from standard‐exposure CNI to sirolimus with low‐dose CNI or with MMF in a CNI‐free regimen , but although efficacy appeared acceptable, the number of patients and rejection episodes was low, limiting interpretation (Table ).…”
Section: Efficacy Of Mtor Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective single‐center studies in which maintenance pediatric kidney transplant patients have been switched from a standard CNI regimen to an mTOR inhibitor with low‐dose CNI therapy or, more frequently, CNI‐free immunosuppression after introduction of everolimus or sirolimus have indicated that rejection is prevented effectively after conversion, but have generally included no more than 30 patients. Two prospective trials have evaluated conversion of patients from standard‐exposure CNI to sirolimus with low‐dose CNI or with MMF in a CNI‐free regimen , but although efficacy appeared acceptable, the number of patients and rejection episodes was low, limiting interpretation (Table ).…”
Section: Efficacy Of Mtor Inhibitorsmentioning
confidence: 99%
“…in 20 unselected de novo patients who received everolimus with reduced cyclosporine and steroid elimination after six months (mean estimated GFR 71 mL/min/1.73 m 2 at one yr, 61 mL/min/1.73 m 2 at three yr) . In the maintenance setting, switch from CNI therapy to sirolimus in one prospective and two large retrospective single‐center studies has been shown to improve graft function based on estimated GFR even in patients converted at up to three yr post‐transplant , although no benefit vs. MMF therapy was seen in a randomized trial of 20 patients followed for two yr .…”
Section: Renal Functionmentioning
confidence: 99%
“…The study in this issue of Pediatric Transplantation (8) is important in several aspects: (i) in this large cohort of pediatric kidney transplant patients, with biopsy‐proven grade 1 CAN, glomerular filtration rate (GFR) increased and proteinuria did not change following conversion from CNIs to SRL, (ii) lower GFR and higher levels of proteinuria were predictors of graft loss after conversion, (iii) the rate of acute rejection episodes was low, and (iv) side effects were frequent but mostly mild.…”
Section: Which Would Be the Best Strategy To Prevent Can?mentioning
confidence: 99%